2017
DOI: 10.3390/insects8020058
|View full text |Cite
|
Sign up to set email alerts
|

Termite Species Distribution and Flight Periods on Oahu, Hawaii

Abstract: Termites are economically-important structural pests, costing residents of Hawaii over $100 million annually. On Oahu, the last published termite swarming survey occurred from 1969 to 1971, and the last termite hand-collection survey occurred from 1998 to 2000. To contribute data on termite occurrences on Oahu, a light-trap survey took place from February 2011 to September 2012, and a hand-collection survey occurred from September to November 2012. Formosan subterranean termite, Coptotermes formosanus Shiraki,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Carvacrol has been shown to produce potent, acute toxicity to insects, nematodes, and mites [95]. It causes positive allosteric modulators in insects to bind to γ-aminobutyric acid, causing inhibitory symptoms in the nervous system [3]. Carvacrol caused 100% mortality of Odontotermes assamensis Holmgren (Blattodea: Termitidae) at 2.5 mg/g after 8 days [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carvacrol has been shown to produce potent, acute toxicity to insects, nematodes, and mites [95]. It causes positive allosteric modulators in insects to bind to γ-aminobutyric acid, causing inhibitory symptoms in the nervous system [3]. Carvacrol caused 100% mortality of Odontotermes assamensis Holmgren (Blattodea: Termitidae) at 2.5 mg/g after 8 days [42].…”
Section: Discussionmentioning
confidence: 99%
“…Termites, although important in ecosystems, are economically important structural pests to wood and cellulosic material in service [1][2][3][4][5][6]. Bir al-Shaghala cemeteries, located to the west of the city of Mut, 3 km from Dakhla Oasis, Egypt, are the site of heavy infestation by the termite Microcerotermes eugnathus Silvestri (Blattodea, Termitidae) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of precipitation in areas with marked seasonality is generally expected to be the main variable influencing this activity since the flight period of most species is associated with the rainy season (Nutting & Haverty 1976;Nutting 1979) and the flights of some species occur shortly after precipitation events (Nalepa et al 2001;Mitchell 2008;Harit et al 2014). However, some studies have shown that several other environmental factors can act as predictors of these events, such as temperature, humidity and, less frequently, wind speed and atmospheric pressure (Nutting 1969;Medeiros et al 1999;Martius 2003;Neoh & Lee 2009;Nasir & Akhtar 2011;Tong et al 2017;Sugio et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Major drywood termite species found in Hawaii include Cryptotermes brevis, Incisitermes immigrans, and Neotermes connexus [1][2][3]. Among these species, the West Indian dry-Insects 2021, 12, 1090 2 of 12 wood termite, C. brevis, is the most damaging and prevalent in structures and has been recorded in Hawaii since 1884 [4].…”
Section: Introductionmentioning
confidence: 99%